Learning Jawi System (LJS) using ARM board under Linux - Noor Shalasiah, Osman; Rohani, S Mohammed Farook; Zulkifli, Husin (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.